Geopolitik Indonesia dalam Landasan Idil Pancasila - Firdianti; Fredik L. Kollo; Anjulin Y Kamlasi; Maria Cindiany Baru; Maria Kartika Jinas; Irfan H. Ollo (Penerbit STKIP PGRI Bangkalan, 2025)
This study stems from the fact that increasingly complex global geopolitical developments require Indonesia to have a strategic orientation rooted in the values of Pancasila. This study aims to analyse the relationship between Indonesian geopolitics and the idealistic foundation of Pancasila as a moral and ideological basis for shaping national policy direction. The method used in this study is library research with a descriptive-analytical approach, which involves analysing various relevant scientific literature, books, and academic articles to gain a deep conceptual understanding. The results of the study show that Pancasila functions as a moral and ideological guideline that guides the Indonesian people in viewing the archipelago as a whole and determining the direction of political, economic, social, and defence policies oriented towards unity, justice, and the welfare of the people. In addition, the values of Pancasila also serve as an ethical foundation in facing various modern geopolitical challenges so that national policies remain consistent with the values of humanity and social justice. Thus, Indonesia's geopolitics based on Pancasila reflects the identity of a sovereign nation with character that upholds world peace.